Quantitative trait loci associated with fatness in a broiler-layer cross - Campos, R. L. R.; Nones, K.; Ledur, M. C.; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Pinto, L. F. B.; Ambo, M.; Boschiero, C. [UNESP]; Ruy, D. C.; Baron, E. E.; Ninov, K.; Altenhofen, C. A. B.; Silva, R. A. M. S.; et al. (Wiley-Blackwell Publishing, Inc, 2009)
P>An F(2) population established by crossing a broiler male line and a layer line was used to map quantitative trait loci (QTL) affecting abdominal fat weight, abdominal fat percentage and serum cholesterol and triglyceride concentrations. Two genetic models, the line-cross and the half-sib, were applied in the QTL analysis, both using the regression interval method. Three significant QTL and four suggestive QTL were mapped in the line-cross analysis and four significant and four suggestive QTL were mapped in the half-sib analysis. A total of five QTL were mapped for abdominal fat weight, six for abdominal fat percentage and four for triglyceride concentration in both analyses. New QTL associated with serum triglyceride concentration were mapped on GGA5, GGA23 and GG27. QTL mapped between markers LEI0029 and ADL0371 on GGA3 for abdominal fat percentage and abdominal fat weight and a suggestive QTL on GGA12 for abdominal fat percentage showed significant parent-of-origin effects. Some QTL mapped here match QTL regions mapped in previous studies using different populations, suggesting good candidate regions for fine-mapping and candidate gene searches.
Keywords: abdominal fat; broiler; chicken; imprinting; layer